2006
DOI: 10.1103/physrevc.74.034323
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ω meson self-coupling on the properties of finite nuclei and neutron stars

Abstract: The effects of ω meson self-coupling (OMSC) on the properties of finite nuclei and neutron stars are investigated within the framework of effective field theory based relativistic mean-field (ERMF) model which includes the contributions from all possible mixed interactions between the scalar-isoscalar (σ), vector-isoscalar (ω) and vector-isovector (ρ) mesons upto the quartic order.For a realistic investigation, several parameter sets corresponding to different values of OMSC are generated by adjusting the rema… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 37 publications
2
36
0
Order By: Relevance
“…This is an alternative to the often-used method of constraining K 0 directly from its correlation with E GMR . Following this new approach, and by using experimental data of E GMR for 208 Pb, [112][113][114][115][116][117][118][119][120][121][122][123][124] Sn isotopes, 90 Zr, and 144 Sm, the linear correlation of E GMR and M c shown in Refs. [11,12] was used to constrain M c to the range M c = 1100 ± 70 MeV.…”
Section: B Updated Constraints: Set2a and Set2bmentioning
confidence: 99%
“…This is an alternative to the often-used method of constraining K 0 directly from its correlation with E GMR . Following this new approach, and by using experimental data of E GMR for 208 Pb, [112][113][114][115][116][117][118][119][120][121][122][123][124] Sn isotopes, 90 Zr, and 144 Sm, the linear correlation of E GMR and M c shown in Refs. [11,12] was used to constrain M c to the range M c = 1100 ± 70 MeV.…”
Section: B Updated Constraints: Set2a and Set2bmentioning
confidence: 99%
“…The equations of state for these groups, e.g., the energy density and pressure, are calculated from the energy-momentum tensor (in the mean-field approximation): E = T 00 , and P = The results obtained were the following: out of 147 models only 9 of them satisfies all the constraints, excluding the constraint related to K τ,v (isospin dependence of the incompressibility) [1]. These are: BSR15, BSR16, BSR17 (5% of tolerance in the PNM2 constraint -see [1]), BSR18 (5% of tolerance in the PNM2 constraint -see [1]) [2], DD-F, [5] FSUGold, [6] FSUGold4, [7] FSUGZ06, [8] and TW99 [3]. Their nuclear matter properties are given in Table 1.…”
mentioning
confidence: 99%
“…The results are also compared to the corresponding experimental data. It is found that none of the published E-RMF parameter sets [10][11][12]14] were simultaneously compatible with all the constraints mentioned; but by fine tuning some parameters of the E-RMF model, agreement with experimental data has been achieved.…”
Section: Introductionmentioning
confidence: 98%
“…After that, several parameter sets of the model were introduced [11,12]. The parameter sets of the E-RMF model provide a good description of many ground-state properties of medium to heavy nuclei [10][11][12][13]. Efforts to improve the model's weakness in the isovector sector have also been made [12,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation